2016
DOI: 10.1111/cas.12880
|View full text |Cite
|
Sign up to set email alerts
|

Novel combination of serum microRNA for detecting breast cancer in the early stage

Abstract: MicroRNA (miRNA), which are stably present in serum, have been reported to be potentially useful for detecting cancer. In the present study, we examined the expression profiles of serum miRNA in several large cohorts to identify novel miRNA that can be used to detect early stage breast cancer. We comprehensively evaluated the serum miRNA expression profiles using highly sensitive microarray analysis. A total of 1280 serum samples of breast cancer patients stored in the National Cancer Center Biobank were used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
259
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 292 publications
(280 citation statements)
references
References 24 publications
10
259
0
Order By: Relevance
“…Particularly, many miRNAs including miR-1307 have been linked to chemo-resistance to many kinds of chemotherapy drugs in ovarian cancer [2, 4, 79, 1316]. Recently, miR-1307 was found to be up-regulated in a variety of cancers, such as breast cancer, liver cancer, colorectal tumor and ovarian cancer [7, 2124]. For example, miR-1307-3p was found to be useful for detecting breast cancer in the early stage [21].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, many miRNAs including miR-1307 have been linked to chemo-resistance to many kinds of chemotherapy drugs in ovarian cancer [2, 4, 79, 1316]. Recently, miR-1307 was found to be up-regulated in a variety of cancers, such as breast cancer, liver cancer, colorectal tumor and ovarian cancer [7, 2124]. For example, miR-1307-3p was found to be useful for detecting breast cancer in the early stage [21].…”
Section: Discussionmentioning
confidence: 99%
“…This miRNA has also an impact on metastasis-free survival and event-free survival rates, independently of ER status [154]. Hsa-miR-1246 was included in a 5-miRNA signature with good diagnostic features, able to discriminate between healthy and early stage BC samples [155]. …”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that exosomal miRNAs can be detected in a variety of body fluids, from blood to breast milk, and that their levels are correlated with patient status [4,5,[60][61][62][63][64][65][66][67][68][69][70][71][72][73] (Table 1). On January 21, 2016, cancer diagnosis using exosomes from blood became commercially available in the US (http://www.exosomedx.com) [6].…”
Section: Diagnosismentioning
confidence: 99%
“…Like cellular miRNA expression profiles, the expression profiles of cell-free and circulating miRNAs are also correlated with the pathological condition of cancer patients [4,60]. Therefore, a considerable amount of research has been expended in trying to develop novel methods for the detection and characterization of microvesicles in the blood of patients classified according to clinical stage [74][75][76].…”
Section: Diagnosismentioning
confidence: 99%